MAKNA KALIMAT PERINTAH DALAM KITAB “ASBAB WURUD AL-HADIS” (KAJIAN SEMANTIK) - Indah Fadilah; Mohammad Badrus Sholih (Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2022)
This article aims to describe the characteristics and meanings of the imperative sentences in the book